The Influence of Trust in Traditional Contracting: Investigating the "Lived Experience" of Stakeholders (Construction Economics and Building, 2015)
The traditional procurement approach is ever-present within the construction industry. With fundamental design principles founded on definitive risk allocation, this transactional based approach fails to acknowledge or foster the cooperative relationships considered to be vital to the success of any project. Contractual design encourages stakeholders to defend their own individual interest to the likely detriment of project objectives. These failings are not disputed, however, given that trust is a fundamental requirement for human interaction the influence of trust is potentially important in terms of stakeholder relationships and ultimate project success. Trust is therefore examined within this context. A conceptual framework of trust is presented and subsequently used to code and analyse detailed, semi-structured interviews with multiple stakeholders from different projects. Using a phenomenological investigation of trust via the lived experiences of multiple practitioners, issues pertaining to the formation and maintenance of trust within traditionally procured construction projects are examined. Trust was found to be integral to the lived experiences of practitioners, with both good and bad relationships evident within the constructs of traditional procurement mechanisms. In this regard, individual personalities were considered significant, along with appropriate risk identification and management. Communication, particularly of an informal nature, was also highlighted. A greater emphasis on project team selection during the initial stages of a project would therefore be beneficial, as would careful consideration of the allocation of risk. Contract design would also be enhanced through prescriptive protocols for developing and maintaining trust, along with mandated mechanisms for informal communication, particularly when responding to negative events. A greater understanding regarding the consequences of lost trust and the intricacies of trust repair would also be of value.